Convergent evolution of sexual dimorphism in species of the family Dolichopodidae (Diptera) - Mariya Alexandrovna Chursina (Society for Indonesian Biodiversity, 2019)
Abstract. Chursina MA. 2019. Convergent evolution of sexual dimorphism in species of the family Dolichopodidae (Diptera). Biodiversitas 20: 2480-2485. In this study, we investigated patterns of sexual dimorphism in four dolichopodid species namely Dolichopus acuticornis Wiedemann, 1817, D. longicornis Stannius, 1831, Rhaphium appendiculatum Zetterstedt, 1849, and R. caliginosum Meigen, 1824 that are exhibiting similar patterns of sexual dimorphism. Although they are distantly related, males of all these species exhibit similar sexual dimorphic characters in term of elongation of postpedicel. A comparison of variation made it possible to assumed that although sexual selection acts differently, all four species exhibited similar patterns of sexual dimorphism in wings and legs; females possessed relatively widened wing and elongated fore and hind femora than males. Cluster analysis for the morphometry data demonstrated that the differences between sexes significantly exceeds the differences between species. These results may reflect the presence of some conservative genetic structure of covariation among characters.